ANALISIS GAYA BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPAS SEKOLAH DASAR - Fany Karina Agustin; Dudung Suryana; Rizki Hadiwijaya Zulkarnaen (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Ecosystem material in class III elementary school is designed to build students' awareness of environmental balance through concrete experiences, simple experiments and direct observation. However, the reality in the field is that students often do not understand ecosystem concepts well, which causes learning to be less than optimal. One of them is the diversity of students' learning styles which has not been fully considered by teachers. Then, limited classroom space makes it difficult for teachers to provide sufficient movement and practice opportunities for students. The aim of this research is to determine students' learning styles, the factors that influence them, and the learning strategies that can be applied. The research method used is a descriptive qualitative method. Data collection techniques through questionnaires, observation, interviews and documentation. Data validity is carried out through source triangulation. The data analysis techniques used consist of data reduction, data presentation, and conclusions/verification. The results of the research showed that the learning style of class III students at SDN Kotabaru in science and science learning on ecosystem material consisted of 20 auditory students (51.3%), 13 visual students (33.3%), and 6 kinesthetic students (15.4%). There are two factors that influence students' learning styles. Internal factors; (psychological) where students tend to like the teacher's verbal explanations, discussions and direct practice, as well as optimal physical factors due to the absence of visual, hearing or physical disabilities that hinder the learning process. External factors; (family) where parents only tell them to study without active assistance or providing a special study room, as well as classroom conditions full of 39 students causing problems with concentration and difficulties for educators in implementing the differentiation method. The station rotation learning strategy is able to overcome these obstacles.